The impacts of inflation on poverty and income distribution in ASEAN - Nur Aireen Syahirah, Azhar (2020)
The purpose of this paper is to study the impact of inflation on poverty in selected ASEAN countries. Emulating Talukdar (2012), the paper analyses the impact of inflation on poverty and income distribution of eight ASEAN countries using the Country and Period Fixed Effect Panel Least Squares Model. The panel dataset comprises of ten observations over the period of 1999 to 2018 for each country, with the analysis restricted to only eight members of ASEAN, namely Malaysia, Indonesia, Thailand, the Philippines, Myanmar, Vietnam, Lao People’s Democratic Republic and Cambodia to study the impact of inflation on a region with differing income and poverty level. Besides inflation, the existing literature highlight that poverty is influenced by various factors, including income, external debt, and education level. Therefore, the paper has utilized inflation as the main independent variable, poverty as the dependent variable, while the rest are used as control variables. Through Panel Least Squares Regression Analysis, it is concluded that inflation is negatively correlated to poverty while income, external debt and educational attainment show a negative correlation with poverty.